Salinomycin inhibits Wnt signaling and selectively induces apoptosis in chronic lymphocytic leukemia cells - Lu, Desheng; Choi, Michael Y; Yu, Jian; Castro, Januario E; Kipps, Thomas J; Carson, Dennis A (Proceedings of the National Academy of Sciences - PNAS, 2011)
Salinomycin, an antibiotic potassium ionophore, has been reported recently to act as a selective breast cancer stem cell inhibitor, but the biochemical basis for its anticancer effects is not clear. The Wnt/Î²-catenin signal transduction pathway plays a central role in stem cell development, and its aberrant activation can cause cancer. In this study, we identified salinomycin as a potent inhibitor of the Wnt signaling cascade. In Wnt-transfected HEK293 cells, salinomycin blocked the phosphorylation of the Wnt coreceptor lipoprotein receptor related protein 6 (LRP6) and induced its degradation. Nigericin, another potassium ionophore with activity against cancer stem cells, exerted similar effects. In otherwise unmanipulated chronic lymphocytic leukemia cells with constitutive Wnt activation nanomolar concentrations of salinomycin down-regulated the expression of Wnt target genes such as LEF1, cyclin D1, and fibronectin, depressed LRP6 levels, and limited cell survival. Normal human peripheral blood lymphocytes resisted salinomycin toxicity. These results indicate that ionic changes induced by salinomycin and related drugs inhibit proximal Wnt signaling by interfering with LPR6 phosphorylation, and thus impair the survival of cells that depend on Wnt signaling at the plasma membrane.